Silicon Mitigates the Effects of Water Deficit in Tropical Plants - Marques Teixeira, Gelza Carliane [UNESP]; de Mello Prado, Renato [UNESP] (Springer Nature, 2023)
The objective of this revision is to address the potentials of this new form of application of Si via fertigation to improve the Si use efficiency in irrigated agriculture aiming to mitigate damage caused by water deficit and to show the need for further studies aiming to reduce irrigation depths for different cultivated species depending on the type of soil. It is important to emphasize that Si can enhance plant growth even in optimal water conditions, increasing the response of crops possibly because it favors other production factors that are not yet studied.
Keywords: Fertigation; Irrigated system; Si; Soil water content